A reconstrução de um espaço histórico : o concelho de Cambra na 2ª metade do século XVIII : fontes e metodologia - Amorim, Inês (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The territorial reconstruction of the municipality of Cambra will allow a contribution to the diachronic recognition of the organisation levels of its space, identifying the multiple jurisdictions that make the reconstitution of the municipal realities difficult. One seeks to, in a micro-historical analysis, utilise materials and apply methodologies that contribute to an evolutive view of the local space, designing them in a georeferenced way.